2011
DOI: 10.1016/j.neuron.2010.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Functional Architecture of Olfactory Ionotropic Glutamate Receptors

Abstract: Ionotropic glutamate receptors (iGluRs) are ligand-gated ion channels that mediate chemical communication between neurons at synapses. A variant iGluR subfamily, the Ionotropic Receptors (IRs), was recently proposed to detect environmental volatile chemicals in olfactory cilia. Here we elucidate how these peripheral chemosensors have evolved mechanistically from their iGluR ancestors. Using a Drosophila model, we demonstrate that IRs act in combinations of up to three subunits, comprising individual odor-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
774
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 501 publications
(826 citation statements)
references
References 66 publications
43
774
8
1
Order By: Relevance
“…DmelIR84a• DmelIR8a-expressing oocytes generated robust currents (253 ± 26 nA, 1 μM; 1,616 ± 294 nA, 10 μM; and 3,783 ± 159 nA, 100 μM) to phenylacetaldehyde, in agreement with a previous report (6). Although CquiIR40a coexpressed with DmelIR8a remained silent, DmelIR84a coexpressed with CquiIR8a responded to phenylacetaldehyde (717 ± 166 nA, 1 mM), thus suggesting that CquiIR8a was indeed functional.…”
Section: Resultssupporting
confidence: 91%
“…DmelIR84a• DmelIR8a-expressing oocytes generated robust currents (253 ± 26 nA, 1 μM; 1,616 ± 294 nA, 10 μM; and 3,783 ± 159 nA, 100 μM) to phenylacetaldehyde, in agreement with a previous report (6). Although CquiIR40a coexpressed with DmelIR8a remained silent, DmelIR84a coexpressed with CquiIR8a responded to phenylacetaldehyde (717 ± 166 nA, 1 mM), thus suggesting that CquiIR8a was indeed functional.…”
Section: Resultssupporting
confidence: 91%
“…S1 and S2). This probability value of mEGFP being fluorescent is similar to what was observed previously for mEGFP fused to a number of other membrane proteins (28)(29)(30)(31)(32)(33). Binomial predictions based on four subunits also accounted well for the other hBest family members ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…Although earlier biochemical studies concluded that the Best1 channel is an oligomer, the estimate of the number of subunits ranged from 2 to 5 (22,27). To resolve this question, we used the single-molecule subunitcounting method (28)(29)(30)(31)(32)(33) to determine the number of subunits by counting the number of fluorescence-bleaching steps of monomeric enhanced green fluorescent protein (mEGFP)-tagged hBest1 in Xenopus oocytes [EGFP-tagged hBest1 was previously shown to be functional (34)]. The main advantages of this method are that: (i) the counting uses Total Internal Reflection Fluorescence Microscopy (TIRFM) to focus exclusively on functional channels in their native physiological environment, the plasma membrane of live cells, and (ii) because the level of expression can be easily controlled in oocytes, it is possible to obtain low enough densities so that each channel appears as an individual fluorescent spot that can be readily resolved from its neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the other member of the family, CquiIR8a, was highly enriched in antennae (mod_lfc, 7.3). Heterologous expression in Xenopus laevis oocytes clearly demonstrated that only when coexpressed with DmelIR8a, the receptor DmelIR75a responded to propionic acid, whereas DmelIR84a·DmelIR8a was activated by phenylacetaldehyde (28). Mutations in DmelIR8a as well as DmelIR25a eliminated responses in IR-expressing OR neurons in D. melanogaster (28), thus both DmelIR8a and DmelIR25a are considered to be coreceptors, although evidence in heterologous system is still lacking for the latter.…”
Section: Odorant-binding Proteins Highly Expressed In Antennae and Legsmentioning
confidence: 99%